Dampak Jenis dan Kualitas Gabah Mempengaruhi Tingkat Harga Gabah dalam Perspektif Ekonomi Syariah di Desa Talungeng Kecamatan Barebbo Kab. Bone - Wiwijianti Wiwijianti; Agussalim Agussalim (Institut Agama Islam Negeri (IAIN) Bone, 2019)
This study discusses the Impact of Grain Types and Quality Affecting Grain Levels in a Sharia Economic Perspective in Talungeng Village, Barebbo District, Kab. Bone, with the aim of research is to know the impact of grain type and quality affecting the level of grain prices and know the Islamic economic review of the impact of grain type and quality. The results showed that the impact of grain type and quality was very dependent on the selection of rice seeds / seeds to be planted in the fields, because of the variety of species favored by farmers, some were short-term and resistant to paddy disease. The names of seeds are: 66, Impari, Cengelis, and Celiung. While the quality depends on the way of maintenance in terms of providing fertilizer, poisons and water supply. Whereas in sharia economics the type and quality of grain is discipline and honesty of farmers in managing rice fields so that they are able to produce rice that fits the needs of the community and has a blessing value in it.